2010
DOI: 10.1002/lsm.20941
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level laser therapy in chronic autoimmune thyroiditis: A pilot study

Abstract: The preliminary results indicate that LLLT promotes the improvement of thyroid function, as patients experienced a decreased need for LT4, a reduction in TPOAb levels, and an increase in parenchymal echogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…An initial pilot trial [89] used 10 applications of PBM (830 nm, 50 mW, 38–108 J/cm 2 ), twice a week, using either the punctual technique (8 patients) or the sweep technique (7 patients). Patients required a lower dosage of levothyroxine, and showed an increased echogenicity by ultrasound.…”
Section: Clinical Applications Of Pbm For Inflammationmentioning
confidence: 99%
“…An initial pilot trial [89] used 10 applications of PBM (830 nm, 50 mW, 38–108 J/cm 2 ), twice a week, using either the punctual technique (8 patients) or the sweep technique (7 patients). Patients required a lower dosage of levothyroxine, and showed an increased echogenicity by ultrasound.…”
Section: Clinical Applications Of Pbm For Inflammationmentioning
confidence: 99%
“…Recent evidences have suggested that low-level laser therapy (LLLT) may improve thyroid function and reduce the levels of thyroid peroxidase antibodies (TPOAb) in patients with hypothyroidism caused by CAT [6, 7]. Color Doppler ultrasound (CDU) provides important additional information beyond that obtained by B-mode ultrasound, allowing the evaluation of various parameters of thyroid vascularization.…”
Section: Introductionmentioning
confidence: 99%
“…12 We assumed that LLLT applied to the lower face could lead to indirect exposure of the thyroid gland, as 830 nm wavelength lasers can reach deeper planes and exert both local and systemic effects. 5,6,[28][29][30]36,38 The rabbit model was chosen because of the previously reported ease of handling, surgical preparation, and postoperative follow-up. 8,28,34,38 Moreover, the size of these animals enabled the use of conventional implants available for clinical use in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effect of infrared laser irradiation directly on the thyroid gland have shown increased mitotic activity in follicular cells, transient hyperactivity of some thyroid follicles, 32,33 and changes in circulating serum levels of the hormones secreted by the thyroid gland, triiodothyronine (T3) and thyroxine (T4). [34][35][36] These findings prompted the present study, as the thyroid gland is located near the mandibular region, a frequent site of irradiation after dental procedures. The objective of this study was to assess the side effects or systemic effects of LLLT used after mandibular dental implant insertion to improve osseointegration through a systematic assessment of circulating serum levels of T3, T4, and calcium in a rabbit model after three different protocols of low-level laser irradiation of the area of implantation of the osseointegrated implant placed immediately into the fresh extraction socket of the mandibular left incisor.…”
Section: Introductionmentioning
confidence: 92%